Pemahaman Pentingnya Generasi Accounting yang Berintegritas dan Kompetitif dalam Pengembangan Bisnis Skala Kecil - Carmidah Carmidah; Yusuf Abdurrahman; Nur Baiti; Muhammad Fatihul Khoir; Farhah Miftahusifa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The development of a mentality towards accounting generation is very important in facing the industrial revolution 4.0. Related to the issues circulating regarding the 4.0 industrial revolution where accounting jobs will be washed away by machines, the anxiety of training graduates about their shadow regarding the 4.0 era where accounting jobs will later be folded by machines, they are worried that when that really happens then jobs what will they get. This article describes the community service program, especially for accounting students at SMKN 1 SEKAMPUNG street Wonosari Indah, Wonokarto, Sekampung, East Lampung. The method used is face-to-face where we provide guidance and strengthen the mentality of them, about how the job prospects for an accounting graduate are either in a company or when they want to develop their own company, therefore they need guidance on how they can use marketing strategies that are often used by a company